Vamping the stage : female voices of Asian modernities - Weintraub, Andrew N. (Andrew Noah); Barendregt, Bart A., 1968- (University of Hawaiʻi Press, 2017)
The emergence of modernity has typically focused on Western male actors and privileged politics and economy over culture. The contributors to this volume successfully unsettle such perspectives by emphasizing the social history, artistic practices, and symbolic meanings of female performers in popular music of Asia. Women surfaced as popular icons in different guises in different Asian countries through different routes of circulation. Often, these women established prominent careers within colonial conditions, which saw Asian societies in rapid transition and the vernacular and familiar articulated with the novel and the foreign. These female performers were not merely symbols of times that were rapidly changing. Nor were they simply the personification of global historical changes. Female entertainers, positioned at the margins of intersecting fields of activities, created something hitherto unknown: they were artistic pioneers of new music, new cinema, new forms of dance and theater, and new behavior, lifestyles, and morals. They were active agents in the creation of local performance cultures, of a newly emerging mass culture, and the rise of a region-wide and globally oriented entertainment industry. Vamping the Stage is the first book-length study of women, modernity, and popular music in Asia, showcasing cutting-edge research conducted by scholars whose methods and perspectives draw from such diverse fields as anthropology, Asian studies, cultural studies, ethnomusicology, and film studies. Led by an impressive introduction written by Weintraub and Barendregt, fourteen contributors analyze the many ways that women performers supported, challenged, and transgressed representations of existing gendered norms in the entertainment industries of China, Japan, India, Indonesia, Iran, Korea, Malaysia, and the Philippines. Placing women's voices in social and historical contexts, the essays explore salient discourses, representations, meanings, and politics of "voice" in Asian popular music. Historicizing the artistic sounds, lyrical texts, and visual images of female performers, the essays reveal how women used popular music to shape the ideas, practices, and meanings of modernity in various Asian contexts and time frames. The ascendency of women as performers paralleled, and in some cases generated, developments in wider society such as suffrage, social and sexual liberation, women as business entrepreneurs and independent income earners, and particularly as models for new life styles. Women's voices, mediated through new technologies of film and the phonograph, changed the soundscape of global popular music and resonate today in all spheres of modern life